Interpreting Surface Structures Using Remote Sensing Technology with Band Combination Technique in Tulehu Geothermal Prospect Area, Maluku - Novranza, Kms; Sudarmo, Haryo Gusmedi; Wahyu, Syafrima; Nadzaruddin, Hikmat (Proceedings of the International Conference on Green Technology, 2017)
Indonesia is a country with the largest geothermal potential in the world. The potential of this geothermal sources is scattered from Sumatera, Java, Sulawesi, Bali, Maluku and Nusa Tenggara. Tulehu is one of geothermal prospect area in Maluku with appearance several surface manifestations such as hot springs, warm springs, and steaming ground. Remote sensing technology can be used to identify lineaments that interpreted as surface structures before doing a direct survey especially geophysical survey in the field. This research uses free Landsat 8 OLI imagery, downloaded from www.earthexplorer.usgs.gov and processed by band combination technique with manual observation. The result of this research shows that the main direction of the lineaments developed in Tulehu geothermal prospect area is Northwest-Southeast and Southwest-Northeast. The result also finds that the lineaments are correlated to the appearance of several surface manifestations. The recommendation of the geophysical survey should be focused on Southeast area.